Dynamic external fixation versus non-operative treatment of severe distal radial fractures - van Dijk, J.P.; Laudy, F.G.J. (Injury, 1996)
Severe distal radius fractures often lead to impairment of wrist function, particularly in younger patients. This paper reports 55 consecutive patients younger than 65 years with displaced intraarticular fractures of the distal radius. Twenty-nine were treated with dynamic external fixation, and 26 with closed reduction and plaster cast immobilization. At least 1 year after the injury the anatomical and functional results were assessed using the scoring system of Lidstrom. In a retrospective analysis, both the anatomical and functional end score were significantly better in the dynamic external fixation group than in the group treated non-operatively (0.02 P < 0.05 using χ 2 analysis with Yates' correction). We conclude that dynamic external fixation is a good alternative for non-operative treatment in younger patients with severe distal radial fractures. Prospective evaluation of this subject is necessary.